Risk Analysis of Work Accidents in Underground Mining - Amelia Dias, Monica; Susilawati, Susilawati (Konsorsium Nasional Pengelola Jurnal Pengabdian, 2023)
Mining is the most dangerous occupational sector in the world. Based on statistical data from the Ministry of Energy and Mineral Resources, in 2019 there were mining accidents that resulted in the death of 24 people, 105 workers heavy, and 28 workers light. The cause of work accidents in the workforce is related to exposure to underground mining toxic gases. This study used the Literature Review (LR) methodology where the data source was obtained from